Children's experiences and expectations of kidney transplantation: A qualitative interview study. Issue 6 (22nd April 2019) - Walker, Rachael C.; Naicker, Derisha; Kara, Tonya; Palmer, Suetonia C.
ABSTRACT: Aim: Kidney transplantation offers improved quality of life and life expectancy compared with dialysis for children. This study aims to understand the experiences and expectations of children during the kidney transplantation process to inform clinical care. Methods: Face‐to‐face, semi‐structured interviews were conducted with 13 children and adolescents aged between 7 and 17 years in New Zealand who had received a kidney transplantation. Findings were conceptualized using thematic analysis with inductive coding. Results: Three major themes were identified: transplant as the goal (the only real treatment and escaping dialysis); dealing with negative emotions (coping with anxiety and fear, guilt for siblings and burden of parent as donor); and enhancing understanding and knowledge (individualised education and reassurance from peer support). Conclusion: Children and adolescents view transplantation as freedom from dialysis and return to a more normal life. Children focus on the positive aspects of transplantation to reduce anxiety and be reassured in the face of uncertainty. Complex emotions arise when thinking about their donor. Children recognize transplantation is not a return to full health and actively seek out ways to self‐manage their care, while remaining anxious about their future. Summary at a Glance: In this study, the authors present a qualitative study of the experiences and expectations of children and adolescents during the kidney transplant process. They concluded that children and adolescents view transplantation as freedom from dialysis and return to a more normal life, while remaining anxious about their future.